113k views
1 vote
2x+3(x-2) - 3(x-6)


A. 2x+12
B. 2x-8
C. 8x - 24
D. 2x - 24

User Dvs
by
5.9k points

2 Answers

6 votes

Answer:

(a) 2x + 12

Explanation:

Let's simplify step-by-step.

2x + 3 (x − 2) − 3 (x − 6)

Distribute:

= 2x + (3)(x) + (3)(−2) + (−3)(x) + (−3)(−6)

=2x + 3x + −6 + −3x + 18

Combine Like Terms:

= 2x + 3x + −6 + −3x + 18

= (2x + 3x + −3x) + (−6 + 18)

= 2x + 12


Hope i helped. have a wonderful day. can i get a brinliest please & thank you.

User Kayas
by
5.6k points
3 votes

The answer is A
2x+12
2x+3(x-2) - 3(x-6) A. 2x+12 B. 2x-8 C. 8x - 24 D. 2x - 24-example-1
User Fang Liu
by
5.0k points